Enhancing performance for three-phase induction motor by changing the magnetic flux density and core material using COMSOL - Firas Saaduldeen Ahmed; Zozan Saadallah Hussain; Truska Khalid Mohammed Salih (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper presents a proposed design and analysis of a three-phase squirrel cage induction motor when changing of internal characteristic design for the three-phase induction motor. Two situations have been applied to enhancing the performance of the three-phase induction motor. The first situation has been implemented by changing the magnetic flux density (MFD) via the build of the six-phase for the same induction motor. The second situation has been implemented by changing core materials of the rotor part of the induction motor, like aluminum (AL) and cast iron (CI). The finite element method (FEM) has been used to analyze the rotor part, also to obtain the representation and simulation of the realty cylindrical rotor part of motor. The frequency domain (FD) analysis using to obtain the results within the environment of the COMSOL multiphysics 5.5 version.